2022
DOI: 10.26858/ijole.v6i2.24757
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Voices of the Use of Facebook and Instagram in Teaching English in the University Context

Abstract: Today the world of social media has immersed in the world of education and influencing the world of the students’ activities. It is inevitable that students in many levels of education have been using social media in their life either as students or as interactants in the certain community. Therefore, it is interesting to see the existence of social media among the students. In this study, the researchers highlight the use of social media among the students in the university. This research applied a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…Social media have become an integral platform for learning and teaching that helps students share ideas, bridge communication gaps, and browse information ( Mahmud et al, 2022 ). Giroux and Moreau (2022) demonstrate teachers’ use of social media to engage students both in structured and unstructured learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Social media have become an integral platform for learning and teaching that helps students share ideas, bridge communication gaps, and browse information ( Mahmud et al, 2022 ). Giroux and Moreau (2022) demonstrate teachers’ use of social media to engage students both in structured and unstructured learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, even though Instagram has not received much attention for learning and teaching, some teachers use it to engage students in learning activities ( Handayani, 2015 ). In the study of Mahmud et al (2022) , classroom teachers asked students to post Instagram stories about their reading activities, including photos of their favorite books and a short book review. Their study reveals that this activity increased student motivation to read and learn.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, some studies that were found were dominantly focusing on peer-assisted learning (PAL) to students' learning outcomes and improvement in secondary and tertiary education level, e.g. Prystiananta (2018), Huriyah et al (1995) and Mahmud and Halim (2022) who revealed the effectiveness of PAL in improving students' English language skills. In relation to the gap, this study seeks for evidence of the solid link between peer-learning implementation in classroom with the ecological aspects of the young language learners (YLL).…”
Section: Peer-learningmentioning
confidence: 99%